Respuesta :

Answer:

x=6

Step-by-step explanation:

3(x-2)=12

divide both sides by 3

x-2=4

add 2 to both sides

x-2+2=4+2

combine like terms

x=6

Answer:

x = 6

Step-by-step explanation:

So the equation looks like this:

3(x - 2) = 12

So the first thing we are going to do in this equation is multiply 3 by x and -2 in order to get rid of the parenthesis:

3(x - 2) = 12

(3 * x) + (3 * (-2)) = 12

3x - 6 = 12

Now we are going to add 6 to -6 and what you to one side of the equation you do to the other:

3x - 6 = 12

    + 6  + 6

3x = 18

Now in order to segregate the variable x from 3 we are going to have to divide 3x by 3 and what you do to one side of the equation you do to the other:

3x/3 = 18/3

x = 6

Now in order to check our work we are going to replace the variable x with six in the equation:

3(x - 2) = 12 = 3((6) - 2) = 12

(3 * 6) + (-2 * 3) = 12

18 - 6 = 12

12 = 12

Tada, hope this helps you!!